2005
DOI: 10.1590/s0102-05362005000300016
|View full text |Cite
|
Sign up to set email alerts
|

Produção de batata-doce em função de doses de P2O5 em dois sistemas de cultivo

Abstract: N a região Nordeste do Brasil, a batata-doce tem alta importância social, por ser uma fonte de alimento energético, e contribuir na geração de emprego e renda, contribuindo para a fixação do homem no campo. No estado da Paraíba é cultivada e difundida principalmente nas regiões próximas aos grandes centros consumidores, especialmente as microrregiões do Brejo e Litoral Paraibano (SOARES et al., 2002), sendo esse Estado considerado o maior produtor nordestino, e o quarto em ní-vel nacional.OLIVEIRA, A.P.; SILVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Santos et al (2006), Oliveira et al (2005a), Oliveira et al (2005b) Houve interação entre fontes de fertilizante e doses nas propriedades químicas do solo, para todas as variáveis avaliadas. Os valores de pH apresentaram resposta estimada segundo modelo quadrático, com valores crescentes até a máxima dose utilizada para a fonte de fertilizante mineral e até aproximadamente 10 t ha -1 para as fontes esterco de galinha e adubação combinada (Figura 2a).…”
Section: Resultsunclassified
“…Santos et al (2006), Oliveira et al (2005a), Oliveira et al (2005b) Houve interação entre fontes de fertilizante e doses nas propriedades químicas do solo, para todas as variáveis avaliadas. Os valores de pH apresentaram resposta estimada segundo modelo quadrático, com valores crescentes até a máxima dose utilizada para a fonte de fertilizante mineral e até aproximadamente 10 t ha -1 para as fontes esterco de galinha e adubação combinada (Figura 2a).…”
Section: Resultsunclassified
“…When sweet potato is grown in soils with adequate P availability, there is generally no positive response to phosphate fertilization. However, in soils with low initial P availability (PMehlich-1 = 3.7 mg dm -3 ), phosphate fertilization significantly increases total storage root yield up to rates close to 259 kg ha -1 P2O5 (Oliveira et al, 2005b). Notwithstanding, a recent study with a new sweet potato cultivar (Beauregard) showed that even in soil with medium initial P availability (Presin = 14 mg dm -3 ), sweet potato responded to rates above 180 kg ha -1 P2O5 (Cruz et al, 2016), i.e., above the recommended for this root crop in soils with medium initial P availability (Lorenzi et al, 1997;Casali, 1999;Silva et al, 2002) (Table 3).…”
Section: Fertilization With Macronutrientsmentioning
confidence: 98%
“…In sweet potato, in addition to improving the yield of storage roots (Oliveira et al, 2005b;Oliveira et al, 2006b;Oliveira et al, 2008), P also interferes with root quality because its supply can increase root starch and total sugar content (Oliveira et al, 2005b;El-Sayed et al, 2011;Abdel-Razzak et al, 2013). However, management of phosphate fertilization in sweet potato must consider the initial soil P availability (soil analysis) since excess P reduces the marketable storage root yield of sweet potato (Oliveira et al, 2005b;Oliveira et al, 2006b;Cruz et al, 2016). This is probably due to the increase in salinity resulting from high concentrations of fertilizers, which reduce storage root growth (Cruz et al, 2016).…”
Section: Fertilization With Macronutrientsmentioning
confidence: 99%
“…O teor de amido também foi influenciado pelas doses de P com a máxima concentração obtida com a dose de 293 kg ha -1 de P2O5. Resultados semelhantes a esses também foram obtidos por Oliveira et al (38) e Oliveira et al (39) .…”
Section: Introductionunclassified